The Effect of Green Intellectual Capital on SMEs’ Business Sustainability - Alfiana Fitri; Erlina Diamastuti; Fitri Romadhon; Husnunnida Maharani (University of Merdeka Malang, 2022)
This study aims to examine the effect of the dimensions of green intellectual capital, i.e. green human capital, green structural capital, and green relational capital, on SMEs’ business sustainability. The data of this quantitative research was collected from a survey of 100 respondents and analyzed by using partial least squares. This study shows that green human capital and green structural capital have no significant effect on SMEs’ business sustainability and that green relational capital influences the sustainability of SMEs’ business. The findings enrich the abundance of knowledge concerning green intellectual capital, especially in the context of SMEs, and prove that green intellectual practices in the SMEs sector are still relatively low. They also imply that SMEs actors should pay more attention to the relational aspect as a relationship with stakeholders is the primary source of strength to win the competition.